Magnesio-ferri-fluoro-hornblende from Portoscuso, Sardinia, Italy: description of a newly approved member of the amphibole supergroup. (2nd January 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ball, Neil A.; Chiappino, Luigi
Abstract: Magnesio-ferri-fluoro-hornblende has the ideal formula A□B Ca2 C(Mg4 Fe 3+ )T(Si7 Al)O22 W F2 (Hawthorne et al., 2012). The holotype sample described in this work occurs as prismatic crystals in vugs of volcanic rocks (Seruci ignimbrites), found along the coast road ∼5.5 km northeast of Portoscuso, Cagliari, Sardinia; associated minerals are tridymite, todorokite, magnetite, and hematite. The name and the mineral were approved by the IMA CNMNC (2014-091). Holotype magnesio-ferri-fluoro-hornblende is monoclinic, space group C2/m, a = 9.839(5), b = 18.078(9), c = 5.319(3) Å, β = 104.99(3)°, V = 913.9(9) Å 3, Z = 2. The density calculated from the empirical formula is 3.315 g cm–3. In plane-polarized light, magnesio-ferri-fluoro-hornblende is pleochroic, X = pale grey (least), Y = dark grey (most), Z = pale brownish grey (intermediate); X^a = 47.6° (β obtuse), Y // b, Z^c = 33.4° (β acute). It is biaxial negative, α = 1.669, β = 1.676, γ = 1.678, all ±0.002; 2Vobs = 74(1)°, 2Vcalc = 56°. The strongest eight lines in the powder X-ray diffraction pattern are [d in Å (I)(hkl)]: 2.711 (100)(151), 8.412 (89)(110), 3.121 (64)(310), 2.553 (61)(2̄02), 3.389 (55)(131), 2.599 (45)(061), 2.164 (36)(261), and 2.738 (34)(3̄31). Electron-microprobe analysis of the refined crystal gave SiO2 45.34, Al2 O3 6.18, TiO2 1.22, FeO 15.24, Fe2 O3 6.27, MgO 9.71, MnO 0.78, ZnO 0.06, CaO 10.18, Na2 O 1.35, K2O 1.15, F 3.22, Cl 0.30, H2Ocalc 0.37, sum 99.95 wt.%. The empirical formula unit, calculated on the basis of 24 (O, OH, F, Cl) apfu with (OH + F + Cl) = 2 apfu is: (Na0.15 K0.22 )∑0.37 (Na0.25 Ca1.66 Mn0.09 )∑2.00 (Mg2.20 Fe 2+ 1.94 Mn0.01 Zn0.01 Fe 3+ 0.72 Ti0.13 )∑5.01 (Al1.11 Si6.89 )∑8.00 O22 [F1.55 (OH)0.37 Cl0.08 )∑2.00.